2006
DOI: 10.1038/sj.onc.1209498
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel (Taxol) upregulates expression of functional interleukin-6 in human ovarian cancer cells through multiple signaling pathways

Abstract: Paclitaxel (Taxol) is an antineoplastic agent that specifically targets microtubules and arrests cells at the G2/M phase of the cell cycle. In addition to mitotic arrest, the activation of c-Jun N-terminal kinase (JNK) signaling pathway has been demonstrated to be involved in the process leading to apoptosis. In an attempt to explore what genes are transcriptionally regulated by the activated JNK signaling pathway upon paclitaxel treatment, we used cDNA microarrays to analyse the changes of gene expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 47 publications
6
59
1
Order By: Relevance
“…Both, JNK and p38 are crucial anti-survival factors in signaling cascades responding to inflammatory cytokines, UV light, cytotoxic drugs and diverse other pro-apoptotic stimuli [28,30,33]. Similarly to our experiments, these pathways were activated in the apoptotic response of various carcinoma cells following treatment with drugs such as Doxorubicin, Paclitaxel, Etoposide [34,35], Aplidin ™ [36], Tamoxifen [37] or Cisplatin (in human ovarian cancer cells) [38]. In the present study we show, by specific inhibition of the activity of p38 MAPK, that the apoptotic response of SKOV-3 ovarian cancer cells to 7Me-IEITC is strongly mediated by the p38 signaling pathway.…”
Section: Discussionsupporting
confidence: 68%
“…Both, JNK and p38 are crucial anti-survival factors in signaling cascades responding to inflammatory cytokines, UV light, cytotoxic drugs and diverse other pro-apoptotic stimuli [28,30,33]. Similarly to our experiments, these pathways were activated in the apoptotic response of various carcinoma cells following treatment with drugs such as Doxorubicin, Paclitaxel, Etoposide [34,35], Aplidin ™ [36], Tamoxifen [37] or Cisplatin (in human ovarian cancer cells) [38]. In the present study we show, by specific inhibition of the activity of p38 MAPK, that the apoptotic response of SKOV-3 ovarian cancer cells to 7Me-IEITC is strongly mediated by the p38 signaling pathway.…”
Section: Discussionsupporting
confidence: 68%
“…9 In contrast, however, paclitaxel mediated LPS-like effects through the TLR4 signaling pathway in an ovarian cancer model. 33 In the present study we have shown for the first time that TLR4 knock-down using siRNA abolished the antiproliferative effects of paclitaxel in primary meningioma cell culture. These data indicate that in human meningiomas paclitaxel mediates a significant degree of its antiproliferative action via TLR4.…”
Section: Discussionmentioning
confidence: 87%
“…Cell suspensions were filtered through a 40 mm filter and analysed for the cell cycle profile with the fluorescence activated cell sorting (FACS) Calibur flow cytometry system (BD, Biosciences, Franklin Lakes, NJ, USA) (Wang et al, 2006).…”
Section: Facs and Cell Cycle Distributionmentioning
confidence: 99%